OBSERVATION OF TWO ENERGY REGIMES BY 90Â° ELECTROSTATIC ENERGY ANALYZER IN REGENERATIVE SOOTING DISCHARGES - Zeeshan, S.; Javeed, S.; Janjua, S. A.; Akhtar, F. (The Nucleus, 2020)
An electrostatic energy analyzer of 90Â°has been designed to measure the energy spread of argon and carbon ion beam from regenerative sooting discharges. Results of energy analyzed ion beam are presented that have been obtained from graphite hollow cathode duoplasmatron ion source and accelerated upto 27 keV. Two groups of low and high-energy ions are observed which are formed inside the ion source. Energy spread increases with increase in energy. Minimum energy spread is 20 eV whereas Maximum is 1.79 keV.